Re-visiting the relationship between oil prices and monetary policy - Hilde Christiane Bjørnland; Jamie Cross; Jonas Hölz (Norges Bank, 2025)
This paper examines how central banks respond to supply-side shocks and investigates the trade-offs they face in stabilizing inflation and output. To do so we develop a dual external instrument proxy structural vector autoregressive (SVAR) model to disentangle the macroeconomic effects of oil supply news and monetary policy shocks. Our identification strategy, which combines multiple external instruments with sign restrictions, enables a sharp distinction between structural shocks, allowing us to analyze their dynamic effects and construct policy counterfactuals for different central bank objectives. We find that both oil supply and monetary policy shocks significantly influence U.S. output and inflation. Moreover, while monetary policy can mitigate some of the output losses caused by oil price shocks, it cannot fully offset their inflationary effects. Finally, we estimate that the Federal Reserve's historical response aligns closely with a policy that places twice as much weight on inflation stabilization than on output stabilization.
hdl:11250/3185116
Keywords: C32; E31; E43; Q41; Q43; 330; Proxy-SVAR; Monetary Policy Instrument; Oil Price Instrument; Counterfactual Analysis; Monetary Policy trade-offs